Influence of an exercise intervention plus an optimal Mediterranean diet adherence during pregnancy on the telomere length of the placenta. The GESTAFIT project. (May 2023) - Flor-Alemany, Marta; Acosta-Manzano, Pedro; Migueles, Jairo H.; Varela-López, Alfonso; Baena-García, Laura; Quiles, José L.; Aparicio, Virginia A.
Abstract: We aimed to investigate whether the effects of exercise on placental relative telomere length (RTL) after delivery are modulated by the Mediterranean diet [MD] adherence in 65 pregnant women (control n = 34, exercise n = 31). No differences were found in placental RTL between the exercise and the control groups ( p = 0.557). The interaction-term between exercise and MD adherence with placental RTL was significant ( p = 0.001). Specifically, women in the exercise group showed longer placental RTL after birth compared to controls (referent group), only for those women with a high MD adherence (mean difference = 0.467, p= 0.010). A concurrent-exercise training plus an optimal MD adherence during pregnancy might prevent the placental RTL shortening. Highlights: The exercise intervention alone did not influence placental telomere length. Diet combined with exercise might prevent placental telomere shortening. The potential role of placental telomere length for child health should be elucidated.